Impact of Street’s Physical Elements on Walkability: a Case of Mawlawi Street in Sulaymaniyah, Iraq (International Journal of Built Environment and Sustainability, 2016)
A pleasant walking environment is a precondition for living in a sustainable city. Appropriate street design can increase quality and quantity of walking. However, the adequacy and quality of physical elements as the most significant components of street can seriously affect walkability in the streets. The objective of this study was to critically assess the walkability level in terms of physical elements of Mawlawi Street, a famous commercial street located in the city center of Sulaymaniyah, Iraq. The qualitative research based on interview with locals, direct observation and quantitative research via questionnaire with pedestrians were conducted in this study. First, site observation was carried out through PEDS (Pedestrian Environment Data Scan) audit tool and the taking of photographs in order to observe the streetscape features. In this regard, four criteria as environment, pedestrian facility, road attributes, walking environment, and subjective assessment were considered as well serving the purpose of providing a broad direction about streetscape features. Then, a 5 point Likert scale questionnaire with pedestrians was conducted to triangulate the findings from observation. Later on, the findings were validated through an interview with locals regarding their subjective ideas about those criteria. The study showed that inadequate and poor quality of street’s physical elements changed the street to an unsafe and uncomfortable environment for walking with weak and low level of street connectivity and accessibility for pedestrians.